1999
DOI: 10.1161/01.cir.100.suppl_2.ii-29
|View full text |Cite
|
Sign up to set email alerts
|

Early and Long-Term Results of a Valve-Sparing Operation for Marfan Syndrome

Abstract: Background-We have previously described the experience, rationale, and development of a valve preserving technique, but its role in patients with Marfan syndrome has not previously been defined. Here, we attempt to determine the early and long-term results, timing, and determinants of outcome of this operation in patients with Marfan syndrome. Methods and Results-Since 1979, 82 patients (73.2% of all patients with Marfan syndrome undergoing resection of aneurysm of the ascending aorta) were operated on using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 18 publications
6
46
0
3
Order By: Relevance
“…The fixation of the aortic ring was considered as the main reason for the lowest incidence of reoperation in patients who underwent reimplantation technique when compared to remodeling technique [12,[18][19][20][21][22]. Several other technical changes were suggested for the reconstruction process of the aortic root with valve preservation and were summarized by Miller [23] in the editorial referred above.…”
Section: (42 -80) (Values In Parentheses With a 95% Confidence Intermentioning
confidence: 99%
“…The fixation of the aortic ring was considered as the main reason for the lowest incidence of reoperation in patients who underwent reimplantation technique when compared to remodeling technique [12,[18][19][20][21][22]. Several other technical changes were suggested for the reconstruction process of the aortic root with valve preservation and were summarized by Miller [23] in the editorial referred above.…”
Section: (42 -80) (Values In Parentheses With a 95% Confidence Intermentioning
confidence: 99%
“…This result was superior to Yacoub's experience, in which 17% of patients required reoperation by 10 years (17 patients at risk at 10 years). 32 In summary, the valve-sparing aortic root replacement presents patients with MFS with a reasonable alternative to CVG. Survival is excellent with either technique and complications are rare, but the long-term durability of this repair has not been established.…”
Section: Valve-sparing Aortic Surgical Repairmentioning
confidence: 97%
“…Recent outcome reports from both Yacoub's and David's institutions indicated that the operative mortality rate for either procedure is low, but the need to return to the operating room for bleeding was 6-fold higher after a Yacoub operation than a David procedure (18% versus 3%). 32,33 Long-term survival was excellent with either technique, especially for prophylactic aortic repairs. Theoretically, valvesparing aortic root replacement should be associated with lower morbidity and mortality when compared with CVG because of the complications associated with a mechanical valve.…”
Section: Valve-sparing Aortic Surgical Repairmentioning
confidence: 97%
See 1 more Smart Citation
“…кардиология и сердечно-сосудистая хирургия, 3,2016 В хирургии аневризм корня аорты (АКА) и недоста-точности аортального клапана (АК) особенно актуальны-ми и востребованными являются клапансохраняющие операции, в основе которых лежат ремоделирование и ре-имплантация корня аорты, описанные М. Якубом [1,8,10] и T. Дэвидом [2][3][4]9]. Низкий процент осложнений, полученный в клиниках с большим опытом реконструк-тивной хирургии, и гемодинамические преимущества де-лают подобные вмешательства крайне привлекательны-ми.…”
unclassified